Decreasing antibiotic over-use by implementation of an antibiotic stewardship programme in preterm neonates in resource limited settings – a quality improvement initiative. (3rd April 2021) - Kommalur, Anitha; Baddadka, Vidyalakshmi; Devadas, Sahana; Kariyappa, Mallesh; Dakshayani, B.; Krishnapura Lakshminarayana, Shilpa; Rao, Suman P. N.; Venkatagiri, Praveen; Devi Chinnappa, Gayathri; Veranna Sajjan, Sushma
ABSTRACT: Background: Antibiotics play a critical role in neonatal sepsis but excessive use is associated with adverse outcomes and the current prescribing rates of antibiotics are unacceptably high. Aim: To reduce antibiotic over-use in preterm neonates by implementing an antibiotic stewardship programme using a quality improvement (QI) initiative. Methods: This study was conducted at a neonatal intensive care unit in a resource-limited setting. The reasons for antibiotic over-use were analysed and an antibiotic stewardship programme was implemented by using a QI initiative. The duration of the QI was a 1-month baseline phase followed by 3 months of implementation which was undertaken in the form of Plan-Do-Study-Act (P-D-S-A) cycles. The sustainment phase was observed for 2 months. All neonates admitted to the preterm unit were included. The outcome measure was the antibiotic usage expressed as days of therapy (DOT)/1000 patient days. Results: In the baseline phase, DOT/1000 patient days was 1464 which fell to 706, 511, and 442 DOT/1000 patient days, respectively, over 3 months, resulting in a 65% reduction in antibiotic usage. This was achieved by a combination of efforts directed towards defining the conditions for no antibiotics, revising existing antibiotic policy, stopping orders at 48 hours, de-escalation to the narrowest spectrum antibiotic, stopping prophylactic antifungal agents and limited use of broad-spectrum antibiotics. The results were achieved without an increase in culture-positive sepsis or mortality. Conclusions: Implementation of a tailored antibiotic stewardship programme through a QI initiative was effective and safe in reducing antibiotic use in preterm neonates in a resource-limited setting. Abbreviations: AIIMS, All India Institute of Medical Sciences; DOT, days of therapy; HIC, high-income countries; ICMR, Indian Council of Medical Research; LMIC, low- to middle-income countries; LOS, late-onset sepsis; NICU, neonatal intensive care unit; NNF, National Neonatology Forum; P-D-S-A, plan-do-study-act; QI, quality improvement; SNCU, Special newborn care unit.